A LSTM-based approximate dynamic programming method for hydropower reservoir operation optimization - Feng, Zhong-kai; Luo, Tao; Niu, Wen-jing; Yang, Tao; Wang, Wen-chuan (Journal of hydrology (Amsterdam), 2023)
•ADP is proposed to avoid the redundant computation in DP’s recursive equation.•LSTM-based response surface model reduces intensive power output calculations.•ADP uses less time to provide satisfying results for hydropower reservoir operation. Dynamic programming (DP) is a classical method developed to address the multi-stage hydropower reservoir operation problem, but still suffers from the serious dimensionality problem where the computational burden increases exponentially with the number of state variables. To improve the DP performance, this paper proposes a LSTM-based approximate dynamic programming (ADP) method for complex hydropower reservoir operation optimization. In ADP, the long short-term memory (LSTM) is treated as the response surface model to reduce redundant computations of power outputs in DP’s recursive equation, making obvious improvements in the execution efficiency. To fully assess its feasibility, the ADP method is used to find the scheduling schemes of a real-world reservoir system in China. Simulation results show that compared with the standard DP method, ADP effectively reduces the execution time while guarantee the solution quality in different cases. In the 1000-state and wet-year scenario, the ADP method achieves approximately 86.7% and 85.8% reductions in DP’s computation time for Longyangxia and Laxiwa reservoir with the goal of maximizing power generation. Thus, the LSTM-based response surface model is an effective tool to improve the DP performance in the hydropower reservoir operation problem.